Effects of a Consensus-Based Pulmonary Embolism Treatment Algorithm and Response Team on Treatment Modality Choices, Outcomes, and Complications. (4th June 2020) - Melamed, Roman; St. Hill, Catherine A.; Engstrom, Bjorn I.; Tierney, David M.; Smith, Claire S.; Agboto, Vincent K.; Weise, Brynn E.; Eckman, Peter M.; Skeik, Nedaa
Pulmonary embolism (PE) treatment depends on disease severity and risk of complications. Physician and institutional expertise may influence the use of reperfusion therapy (RT) such as systemic thrombolysis (SL) and catheter-directed interventions (CDI). We aimed to investigate the effects of a consensus-based treatment algorithm (TA) and subsequent implementation of PE response team (PERT) on RT modality choices and patient outcomes. A cohort of PE patients admitted to a tertiary care hospital between 2012 and 2017 was retrospectively evaluated. Demographics, clinical variables, RT selections, and patient outcomes during 3 consecutive 2-year periods (baseline, with TA, and with TA+PERT) were compared. Descriptive statistics were used for data analysis. A total of 1105 PE patients were admitted, and 112 received RT. Use of RT increased from 4.7% at baseline to 8.2% and 16.1% during the TA and TA+PERT periods. The primary RT modality transitioned from CDI to SL, and reduced-dose SL became most common. Treatment selection patterns remained unchanged after PERT introduction. Hospital length of stay decreased from 4.78 to 2.96 and 2.81 days ( P < .001). Most of the hemorrhagic complications were minor, and their rates were similar across all 3 periods and between SL and CDI. No major hemorrhages occurred in patients treated with reduced-dose SL. In conclusion, TA and PERT represent components of a decision support system facilitating treatment modality selection, contributing to improved outcomes, and limiting complications. Treatment algorithm emerged as a factor providing consistency to PERT recommendations.